2009
DOI: 10.1159/000210554
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Circulating Adhesion Molecule Levels and Albuminuria in Type-2 Diabetic Hypertensive Patients

Abstract: Background/Aims: Endothelial dysfunction, a common feature among hypertensive and type-2 diabetic patients, is associated with inflammation, increased levels of circulating soluble adhesion molecules (SAM), and urinary albumin excretion. The aim of this study was to evaluate the role of circulating SAM levels in the development of albuminuria in hypertensive type-2 diabetic patients. Methods: We studied 30 hypertensive type-2 diabetic patients and 30 non-diabetic normotensive subjects, and measured their VCAM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 28 publications
3
42
1
1
Order By: Relevance
“…Letterio et al [14] discovered that experimental models with impairment in TGF-β 1 gene are highly susceptible to several inflammation resulting in autoimmune diseases and even death [15,16] . El Mesallamy et al [8] correlated TGF-β1 concentrations with Connective tissue growth factor level; their findings showed that between these two molecules there is a closed interaction in DN.…”
Section: Tnf-αmentioning
confidence: 99%
See 1 more Smart Citation
“…Letterio et al [14] discovered that experimental models with impairment in TGF-β 1 gene are highly susceptible to several inflammation resulting in autoimmune diseases and even death [15,16] . El Mesallamy et al [8] correlated TGF-β1 concentrations with Connective tissue growth factor level; their findings showed that between these two molecules there is a closed interaction in DN.…”
Section: Tnf-αmentioning
confidence: 99%
“…ICAM-1 and vascular adhesion molecule-1 (VCAM-1) are involved in the attachment of leukocytes to the vascular wall and penetration into the intima, once there, leukocytes can produce proteolytic enzymes that lead to tissue and organ damage, or differentiate into foam cells that lead to the atherosclerotic process [15] . Several animal models have shown that mice deficient in ICAM-1 are resistant to nephropathy in experimental models of diabetes, while treatment with anti-ICAM-1 monoclonal Ab prevents mononuclear cell infiltration into diabetic glomeruli [3] .…”
Section: Adhesion Moleculesmentioning
confidence: 99%
“…VCAM-1 has been shown in numerous studies to be associated with albuminuria in the general population and in individuals with type 1 and type 2 diabetes mellitus with or without hypertension and IgA nephropathy. 26,[29][30][31][32][33][34] In addition, elevated circulating VCAM-1 has been shown to be correlated with increased VCAM-1 expression from renal biopsy in IgA nephropathy. 35 E-selectin is also found to be a strong predictor of severely increased albuminuria and coronary artery disease in patients with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Egy másik vizsgálatban az ACE-gátló és CCB fi x kombinációja csökkentette a keringő szolúbilis adhéziós molekulákat és nagyobb mértékben csökkentette a transzmembrán glükoproteinekhez tartozó, az atherosclerosis egyik fontos tényezőjének számító VCAM-1-(vascularis sejtadhéziós molekula-1) szintet, mint az ACE-gátló ön-magában [32]. Mivel e mediátorok szerepet játszanak diabetesben és hypertoniában a különböző célszervká-rosodások kialakulásában [33], ezek szintjének csökken-tése preventív hatású lehet.…”
Section: Gyulladáscsökkentő Hatásunclassified